Foundations of the American century : the Ford, Carnegie, and Rockefeller Foundations in the rise of American power - Parmar, Inderjeet (Columbia University Press, 2011)
Inderjeet Parmar reveals the complex interrelations, shared mindsets, and collaborative efforts of influential public and private organizations in the building of American hegemony. Focusing on the involvement of the Ford, Rockefeller, and Carnegie foundations in U.S. foreign affairs, Parmar marks the transformation of America from an?isolationist" nation into the world's only superpower, all in the name of benevolent stewardship. Parmar begins in the 1920s with the establishment of these foundations and their system of top-down, elitist, scientific giving, which focused more on e